2019
DOI: 10.1002/jbmr.3947
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Gut Microbiota and Barrier Function in Glucocorticoid-Induced Osteoporosis

Abstract: Glucocorticoids (GCs) are potent immune‐modulating drugs with significant side effects, including glucocorticoid‐induced osteoporosis (GIO). GCs directly induce osteoblast and osteocyte apoptosis but also alter intestinal microbiota composition. Although the gut microbiota is known to contribute to the regulation of bone density, its role in GIO has never been examined. To test this, male C57/Bl6J mice were treated for 8 weeks with GC (prednisolone, GC‐Tx) in the presence or absence of broad‐spectrum antibioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
137
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(140 citation statements)
references
References 150 publications
(396 reference statements)
3
137
0
Order By: Relevance
“…An association between gut microbiome and skeletal changes has been shown to involve leakage of the intestinal blood barrier and increased circulating endotoxin in estrogen deficiency, glucocorticoid excess, and parathyroid hormone–induced bone anabolism. ( 56–58 ) Whether the intestinal barrier is affected in mice fed the Mont diet is the subject of current studies and would support a connection between activation of anti‐inflammatory pathways and nutrition. Future studies in humans are warranted to examine the effectiveness of blueberry diets on the skeleton, the linkage with microbiome diversity, as well as the sexual dimorphism found in mice in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…An association between gut microbiome and skeletal changes has been shown to involve leakage of the intestinal blood barrier and increased circulating endotoxin in estrogen deficiency, glucocorticoid excess, and parathyroid hormone–induced bone anabolism. ( 56–58 ) Whether the intestinal barrier is affected in mice fed the Mont diet is the subject of current studies and would support a connection between activation of anti‐inflammatory pathways and nutrition. Future studies in humans are warranted to examine the effectiveness of blueberry diets on the skeleton, the linkage with microbiome diversity, as well as the sexual dimorphism found in mice in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…To this regard, two recent studies reported that glucocorticoids induce gut microbial alterations in mice. (Schepper et al, 2019) and humans (Qiu et al, 2019). In human subjects diagnosed for acute transverse myelitis, 3 months treatment with prednisone promoted enrichment in Firmicutes and depletion in Bacteroidetes (Qiu et al, 2019).…”
Section: Drugs Used To Treat Covid-19 and Microbiotamentioning
confidence: 99%
“…Animal models indicate that the absence of a gut microbiota leads to changes in bone remodelling, trabecular bone mineral density and bone volume fraction (Sjogren et al, 2012;Yan and Charles, 2017). Modifications to the gut microbiota have also been shown to reduce bone loss caused by oestrogen depletion (Britton et al, 2014; or glucocorticoid treatment (Schepper et al, 2020), two of the most common contributors to osteoporosis (Marcus, 2013). Changes in the gut microbiome can also mediate the effects of osteoporosis therapies such as the use of PTH (Li et al, 2020;Yu et al, 2020).…”
Section: The Interaction Of the Gut Microbiota With Bonementioning
confidence: 99%